Integration of mass cytometry and mass spectrometry imaging for spatially resolved single-cell metabolic profiling - Nunes, Joana B.; Ijsselsteijn, Marieke E.; Abdelaal, Tamim; Ursem, Rick; van der Ploeg, Manon; Giera, Martin; Everts, Bart; Mahfouz, Ahmed; Heijs, Bram; de Miranda, Noel F. C. C. (Nature methods, 2024)
The integration of spatial omics technologies can provide important insights into the biology of tissues. Here we combined mass spectrometry imaging-based metabolomics and imaging mass cytometry-based immunophenotyping on a single tissue section to reveal metabolic heterogeneity at single-cell resolution within tissues and its association with specific cell populations such as cancer cells or immune cells. This approach has the potential to greatly increase our understanding of tissue-level interplay between metabolic processes and their cellular components. The authors present a workflow integrating imaging mass cytometry and imaging mass spectrometry to deconvolute metabolic heterogeneity at the single-cell level.